Pengembangan Media Pop Up Book Berbasis Augmented Reality (AR) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas IIIPengembangan Media Pop Up Book Berbasis Augmented Reality (AR) untuk Meningkatkan Hasil Belajar Peserta Didik Kelas III - Umu Kulstum; Ina Agustin; Sri Cacik (Advances In Education Journal, 2026)
Early reading skills are the foundation of literacy that determines the success of students' learning at the next level of education. This study aims to analyze the validity level of PAPEMBA (Indonesian Beginning Reading Learning Board) media as an interactive board-based learning media developed to improve the initial reading ability of elementary school grade I students. The research uses a quantitative descriptive approach with data obtained through validation sheets of material experts and media experts. The validation results showed that PAPEMBA media obtained an overall average of 82.67% with a very valid category. In detail, validation by linguists obtained a score of 89% (very valid), media experts of 89% (very valid), and material experts of 70% (valid). These findings show that PAPEMBA media is suitable for use in learning to read in elementary school grade I, with several improvements in the material aspect to be more optimal in supporting the achievement of learning goals.